The Analysis of Understanding Sentence Final Particle âYoâ by Japanese Learners - Nimashita, Hana (Proceedings of the UR International Conference on Educational Sciences, 2018)
This paper investigates the Japanese sentence-final particles âyoâ as they occur in conversation and the equivalent of âyoâ in Indonesian using by Japanese Education students of Riau University. By using theory of sentence final particles presented byMasuoka (1992). This research is a qualitative descriptive research with translation of sentence-final particles âyoâfrom imperative, information and invitation sentences as main data. The result of this research are as follows: first, most of students can not distinguish the function of sentence final particle âyoâ in imperative, information and invitation sentences. Second, the needs of learning improvement in senteces final particle esprecially in grammar and conversation lectures to teach the differences of senteces final particle functions.